How Indonesia Should Go Further with Decentralization: Revisiting the Views and the Visions - Afifi, Abdullah A (IDRIS Darulfunun Institute, 2024)
Indonesia’s vast geography and cultural diversity pose long-standing challenges to the centralized governance systems. Following the collapse of the New Order regime in 1998, the country embarked on an ambitious decentralization campaign, transferring authority and resources from the central government to local governments through Laws No. 22 and 25 of 1999. Despite the progress made, recent trends suggest a drift back toward recentralization and inefficiencies in subnational governance. This article investigates how Indonesia should move forward with a deeper and more coherent decentralization policy, drawing insights from the ideas of key early independence-era thinkers, as well as the reform era. Using a qualitative historical-interpretive approach, the study analyzes political writings, speeches, and conceptual contributions of late figures, framed alongside policy and governance developments in post-Reformasi Indonesia. The findings reveal that decentralization was not merely an administrative concern but a philosophical and moral imperative for these thinkers. Hatta promoted village autonomy; Sjahrir advocated democratic pluralism; Malaka emphasized grassroots empowerment, while the reformists underscored decentralization as a pillar of democratic resilience. The study concludes that Indonesia’s decentralization project must go beyond partial devolution. It should embody the ethical and participatory principles rooted in the country's intellectual tradition that work towards strengthening local democracy, fiscal independence, regional capability, and innovation. Reviving these foundational visions is vital to ensuring that decentralization serves not just efficiency, but also the quality of justice, inclusivity, prosperity, and national diversity.